Tantangan Pemungutan Pajak Mineral Bukan Logam dan Batuan di Kabupaten Tanah Bumbu - Devi Amalia Ramadhan; Muhammad Saleh (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2022)
This research is entitled “The Challenges Of Collecting Non-Metal And Rock Mineral Taxes In Tanah Bumbu District”. The purpose of this study (1) To determine the effectiveness of collecting MBLB Tax as a source of PAD in Tanah Bumbu Regency, (2) To determine the efficiency of the request for MBLB Tax on PAD in Tanah Bumbu Regency, (3) To determine the contribution of the request for MBLB tax to PAD Tanah Bumbu Regency. This study uses primary and secondary data with an annual series (time series) from 2010 to 2020. The source comes from (BPPRD) Tanah Bumbu. The analysis used quantitative descriptive analysis. The results of the research from the side of the effectiveness calculation show that an average of  86.81% is said to be quite effective, for the efficient calculation level the average reaches 9.46% with a category <20% it is said to be inefficient. Meanwhile, the contribution has reached 70.78%,  meaning that it has been able to  meaning that it has been able to make a large contribution  to PAD in Tanah Bumbu Regency.